Prinsip Tanggung Jawab Pengangkut Pada Pengangkutan Laut Di Indonesia - Muhammad Hatta; Dewi Astutty Mochtar; Mohammad Ghufron AZ (Bhirawa Law Journal, 2021)
The carrier as the operator of transportation plays an important role in smoothing the flow of goods and people from one place to another. The safety of goods must be accounted for both to the delivery of the goods and to the parties concerned / interested. In the operation of transporting goods by sea, there is a possibility that losses will beincurred or it can also be called the risk that will always arise. Risks that arise can occur during the process of shipping, loading or unloading or storage. This study uses a normative juridical approach, which analyzes existing legal materials such as laws and regulations, regulations related to the transportation of goods in the field and international agreements. This research examines how the process of carrying out the transportation of shipping goods by sea and how the principle of the responsibility of the carrier in sea transportation according to Law No. 17 of 2008 on shipping. The results of this study consisted of various stages, namely the stages of preparation, loading, transportation, unloading, and completion. Article 57 point 28 of the Job Creation Law requires every ship to have a ship safety certificate. The responsibility ofthe carrier is regulated in Articles 40 and 41 of the Shipping Law and in Article 477 of the Indonesian Commercial Code.